Self-regulation of environmental management : guidelines set by world industry associations for their members' firms : an update 1996-2003 (UN New YorkUS, 2003)
Examines the current guidelines of world industry associations. Includes major areas such as: global environment management; environmentally sound production and consumption patterns; risks and hazards minimization; and full costing.
Bibliography: p. 55